Zinc Acetate Immobilized on Mesoporous Materials by Acetate Ionic Liquids as Catalysts for Vinyl Acetate Synthesis. (17th March 2015) - Xu, Hang; Yu, Tianlong; Li, Mei
Abstract : Ionic liquid containing active ingredient Zn(CH3 COO)2 was loaded in mesoporous silica gel to form supported ionic liquids catalyst (SILC) which was used to synthesize vinyl acetate monomer (VAM). SILC was characterized by 1 HNMR, FT-IR, TGA, BET, and N2 adsorption/desorption and the acetylene method was used to evaluate SILC catalytic activity and stability in fixed reactor. The result shows that 1-allyl-3-acetic ether imidazole acetate ionic liquid is successfully fixed within mesoporous channel of silica gel. The average thickness of ionic liquid catalyst layer is about 1.05 nm. When the catalytic temperature is 195°C, the acetic acid (HAc) conversion is 10.9% with 1.1 g vinyl acetate yield and 98% vinyl acetate (VAc) selectivity. The HAc conversion is increased by rise of catalytic temperature and molar ratio of C2 H2 : HAc and decreased by mass space velocity (WHSV). The catalyst activity is not significantly reduced within 7 days and VAc selectivity has a slight decrease.